PERSEPSI MASYARAKAT REJAI TERHADAP PELAYANAN RUJUKAN KERUMAH SAKIT KABUPATEN LINGGA - Sri Lestari; Nanik Rahmawati; Rahma Syafitri (JURNAL SOSIO-KOMUNIKA, 2023)
This study discusses the perceptions of the community in Rejai Village regarding referrals to the Regional Hospital of Lingga Regency, in this case a referral letter was issued by the UPT Puskesmas Rejai Village. This study used observation techniques and in-depth interviews with 8 informants who were selected purposively (purposive sampling) which were then analyzed descriptively qualitatively. The results showed that the perceptions of the community in Rejai Village towards the referral services provided by the UPT Puskesmas Rejai Village based on the information of some patients who came for treatment said positive things about the Rejai Puskesmas, the patient's perceptions could be seen from the administrative services in carrying out services both from examination and administration clear information given to patients as well as good actions are always maintained by puskesmas employees and speed in work. Part of the patient's perception is that it takes a long time to make a referral letter at the UPT Puskesmas Rejai Village due to the limited medical staff and the community's understanding of making referral letters online. Patients are given drugs according to the disease they are experiencing. Referral letter services are provided if the patient arrives at the UPT Puskesmas whose condition cannot be handled, then the puskesmas provides referrals to the patient to the hospital by consulting the family if necessary, the UPT Puskesmas also provides assistance to the referred patient. It is hoped that in the future the Rejai Village Health Center UPT will have complete facilities and infrastructure and be more active in providing socialization to the community regarding the service process, so that the information provided is easily understood by patients.